Analisis Investasi Saham Syariah Dengan Rasio Fibonacci Dan Fuzzy Logic - Novi Nurul Haibah; Edi Susilo (Jurnal Rekoginisi Ekonomi Islam, 2023)
The investment objective is return, taking into account measurable risk, in the future. The research method uses descriptive quantitative. The purpose of this research is to determine when is the right moment to buy, hold or sell 10 stocks that are consistently listed in the Jakarta Islamic Index (JII) during the 2017-2019 period. The analysis uses the Fibonacci series, and Fuzzy Logic. The results show that the Fibonacci series and Fuzzy Logic can be used as stock valuation instruments relatively, with support and resistance signals. The analysis results recommend ASII and PTBA stock investments